2018
DOI: 10.1007/s00253-018-9395-5
|View full text |Cite
|
Sign up to set email alerts
|

The accD3 gene for mycolic acid biosynthesis as a target for improving fatty acid production by fatty acid-producing Corynebacterium glutamicum strains

Abstract: We have recently developed Corynebacterium glutamicum strains that produce free fatty acids in culture supernatant due to enhanced fatty acid biosynthesis. Of these producing strains, the basic producer PAS-15 has a defect in the gene for a fatty acid biosynthesis repressor protein, and the advanced producer PCC-6 has two additional mutations to augment the production by strain PAS-15. The aim of the present study was to obtain novel genetic traits for improving fatty acid production by these producers.A new m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…These data suggest that fadD5 and fadD15 play significant roles in getting free fatty acids back to their CoA derivatives. Although the pCfadD32 carrier showed a 15% decrease in production, we believed that this was probably due to the redirection of carbon into mycolic acid synthesis, considering the predicted role of FadD32, namely, activation of free fatty acids to form acyl-AMP, a precursor for mycolic acid synthesis ( 14 , 30 ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…These data suggest that fadD5 and fadD15 play significant roles in getting free fatty acids back to their CoA derivatives. Although the pCfadD32 carrier showed a 15% decrease in production, we believed that this was probably due to the redirection of carbon into mycolic acid synthesis, considering the predicted role of FadD32, namely, activation of free fatty acids to form acyl-AMP, a precursor for mycolic acid synthesis ( 14 , 30 ).…”
Section: Resultsmentioning
confidence: 97%
“…To date, however, there have been no reports on their functions, except for fadD32 , which is located in a chromosomal cluster with accD3 and pks (Fig. S1A) and has been assumed to be involved in the synthesis of mycolic acids by activating free fatty acids to form acyl-AMP ( 14 , 30 ). On the other hand, C. glutamicum possesses two annotated tes genes, tesB (Cgl1664, NCgl1600) and tesA (Cgl2451, NCgl2365), whose functions remain to be clarified (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While Jiang et al did not perform whole genome sequencing, Takeno et al reported three mutations in the genes responsible for fatty acid synthesis. Takeno et al repeated the selection step on cerulenin plates and identified one additional mutation. Re‐engineering of this mutation in the previously evolved strain resulted in a 1.2‐fold higher oleic acid titer.…”
Section: Evolutionary Engineering Of Small Molecule Productionmentioning
confidence: 99%